Nutritional and management strategies to optimize growth performance and carcass traits of grow-finish pigs - Cordoba, Hilario Martin (My University, 2024)
This dissertation is comprised of five chapters that evaluate feeder management prior to marketing and dietary interventions to improve carcass yield and reduce feed cost in finishing pigs. In Chapter 1, we implemented feed withdrawal of 12, 18, and 24 h prior to harvest to assess its effect on pig performance, carcass traits, and economic return over two marketing events. Feed withdrawal up to 24 h did not affect carcass characteristics of pigs in the first marketing event, nor did it affect the growth performance of the pigs remaining in the pen and marketed 14 d later. However, a reduction in hot carcass weight was observed in the final marketing event when pigs were withheld from feed for more than 18 h prior to harvest. Chapter 2 evaluated the effects of sulfate and hydroxychloride forms of copper, manganese, and zinc on growth performance, carcass characteristics, and body weight variation in finishing pigs. The use of manganese hydroxychloride, in comparison with the sulfate source, did not affect overall performance or carcass criteria. Similar growth performance was observed when the sulfate and hydroxychloride sources of copper, manganese, and zinc were compared; however, hot carcass weight tended to increase when hydroxychloride forms were used, compared to sulfate sources. Chapter 3 investigated finishing diets differing in Ca:P ratio, added phytase, and 25(OH)D3 levels on pigs' growth performance, body weight variability, serum 25(OH)D3, carcass characteristics, and bone characteristics. We observed that the lowest P level decreased growth performance, carcass weight, bone ash and strength. Also, a 1.1:1 Ca:P ratio reduced feed intake, bone ash and bone strength compared to a 1.25:1 ratio. While serum levels of vitamin D₃ increased when fed 25-hydroxy-D₃, no other benefits in growth performance or bone mineralization were observed. Chapter 4 developed predictive models of growth performance and carcass characteristics of grow-finish pigs in response to dietary net energy using ingredient nutrient values from four different databases. The models demonstrate that increasing dietary NE increased growth performance and carcass responses, except for percentage lean which decreases as NE increased, across the four ingredient databases. Maintaining a Lys:NE ratio influenced the magnitude of change to NE in all responses evaluated as compared to when Lys:NE was not maintained. These models can improve our ability to predict the influence of dietary NE and other nutrients on pig performance and carcass criteria. Chapter 5 compares a central composite design and a factorial arrangement on their ability to predict pig growth performance when feeding variable net energy, soybean meal, and standardized ileal digestible lysine concentrations to pigs weighing 11 to 25 kg. The results showed that the predictors derived from the CCD experiment predicted the performance observed in the factorial arrangement experiment with an accuracy of ± 3% for almost all comparisons. We conclude that both the CCD and factorial arrangement demonstrated the importance of Lys to calorie and crude protein ratio on pig growth performance, indicating that both designs can provide similar results in swine nutrition research.
Keywords: Finishing pigs; Growth; Carcass characteristics; Net energy; Minerals; Lysine